2022
DOI: 10.1039/d2en00104g
|View full text |Cite
|
Sign up to set email alerts
|

Interface engineering of W2C/W2N co-catalyst on g-C3N4 nanosheets for boosted H2 evolution and 4-nitrophenol removal

Abstract: Heterointerface engineering was adopted to obtain W2C/W2N (WCN) particles via the simultaneous carbonization and nitridation process. Superior thin g-C3N4 nanosheets (CN) was employed as the platform to establish Schottky heterojunctions....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…[ 47 ] The charge dynamics was probed by time‐resolved fluorescence decay spectroscopy (Figure 4d). The decay lifetime of BOB and CBOB‐2 were fitted with tri‐exponential equation, [ 48 ] τ 1 , τ 2 , and τ 3 stand for the non‐radiative process, radiative process related to carrier recombination, and energy‐transfer process, respectively. [ 49 ] Comparing BOB and CBOB‐2, τ 1 contributes most to the relaxation process and lasts longer time for CBOB‐2 (Table S2, Supporting Information), which indicates that rapid charge migration occurs at the interface of CBOB‐2.…”
Section: Resultsmentioning
confidence: 99%
“…[ 47 ] The charge dynamics was probed by time‐resolved fluorescence decay spectroscopy (Figure 4d). The decay lifetime of BOB and CBOB‐2 were fitted with tri‐exponential equation, [ 48 ] τ 1 , τ 2 , and τ 3 stand for the non‐radiative process, radiative process related to carrier recombination, and energy‐transfer process, respectively. [ 49 ] Comparing BOB and CBOB‐2, τ 1 contributes most to the relaxation process and lasts longer time for CBOB‐2 (Table S2, Supporting Information), which indicates that rapid charge migration occurs at the interface of CBOB‐2.…”
Section: Resultsmentioning
confidence: 99%
“…5−7 Nevertheless, the low availability of photogenerated carriers of the single-phase LDH-based photocatalysts seriously limits their application. 8−10 To solve these issues, a multitude of strategies, including interfacial engineering, 11,12 defect control, 13,14 element doping, 15,16 morphology regulation, 17 and construction of heterojunctions, 18,19 have been proposed to accelerate the separation and migration of carriers. It is widely known that kinetics and thermodynamics are greatly important for exploring the photocatalytic reaction, and the improvement in photocatalytic activity depends on not only kinetics but also the thermodynamic level.…”
Section: Introductionmentioning
confidence: 99%
“…An appealing and sustainable approach for converting renewable solar energy into chemical energy that can be stored is called photocatalytic H 2 evolution (PHE). Designing and constructing comparable photocatalysts are crucial steps in PHE. Very recently, layered double hydroxide (LDH) materials have emerged as promising photocatalysts for H 2 evolution. Nevertheless, the low availability of photogenerated carriers of the single-phase LDH-based photocatalysts seriously limits their application. To solve these issues, a multitude of strategies, including interfacial engineering, , defect control, , element doping, , morphology regulation, and construction of heterojunctions, , have been proposed to accelerate the separation and migration of carriers. It is widely known that kinetics and thermodynamics are greatly important for exploring the photocatalytic reaction, and the improvement in photocatalytic activity depends on not only kinetics but also the thermodynamic level .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, at present, research work in this area is focused on developing catalysts with high efficiency and stability in an aqueous medium. For this purpose, a lot of researchers have validated that encapsulation of metal complexes inside a carbon-based substrate, such as graphene, carbon nitrides, etc., increases the stability and efficiency of water splitting and supercapacitor applications and other applications. , Among the reported carbon substrate materials, two-dimensional carbon nitride (g-C 3 N 4 ), having higher nitrogen content, is gaining importance as a catalyst for supercapacitor and water-splitting applications in recent times. , However, it possesses fewer active sites and high resistance that limit their applications. To overcome this issue, g-C 3 N 4 combined with metal complexes or metal oxides has been explored and it has been found that the introduction of these catalysts increases its active site, thereby increasing its efficiency. , Several g-C 3 N 4 composites with metal oxides, metals, carbon, and metal phosphides have been studied for water-splitting activity, and it has been found that the catalyst’s incorporation into the g-C 3 N 4 matrix improves the performance.…”
Section: Introductionmentioning
confidence: 99%